Cos(2x) = cos^2(x) - sin^2(x) - cos(x)
but sin^2(x) = 1 - cos^2(x)
cos(2x) - cos(x) = cos^2(x) - (1 - cos^2(x) ) - cos(x)
cos(2x) - cos(x) = cos^2(x) - 1 + cos^2(x) - cos(x)
cos(2x) - cos(x) = 2cos^2(x) - 1 - cos(x)
cos(2x) - cos(x) = (2cos(x) + 1)(cos(x) - 1)
I think this is what you have asked for.
You have to get X all by itself so you divide 20 and 30 which gives you a fraction. X= 20/30
Then = 2/3
D. -48
Put it into your calculator exactly how it is shown up above and you will get the correct answer. Your calculator automatically knows the order of operations.
Answer:
D. negative
Step-by-step explanation:
Let's analyze each answer choice.
A. Zero
A line with a zero slope is a horizontal line. The x values change, but the y values stay the same.
B. Undefined
A line with an undefined slope is a vertical line. The x values don't change and the y values vary.
C. Positive
When a line has a positive slope, the line increases from left to right.
D. Negative
When a line has a negative slope, the line decreases from left to right.
When we move from left to right on the graph, the line moves down. Therefore, this line must have a negative slope and D is correct.
Let
. Then
. Note that
.
Recall that for
, we have
![\displaystyle\frac1{1-x}=\sum_{n\ge0}x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cfrac1%7B1-x%7D%3D%5Csum_%7Bn%5Cge0%7Dx%5En)
This means that for
, or
, we have
![\displaystyle f'(x)=\frac1{1+x^2}=\frac1{1-(-x^2)}=\sum_{n\ge0}(-x^2)^n=\sum_{n\ge0}(-1)^nx^{2n}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%3D%5Cfrac1%7B1%2Bx%5E2%7D%3D%5Cfrac1%7B1-%28-x%5E2%29%7D%3D%5Csum_%7Bn%5Cge0%7D%28-x%5E2%29%5En%3D%5Csum_%7Bn%5Cge0%7D%28-1%29%5Enx%5E%7B2n%7D)
Integrate the series to get
![f(x)=f(0)+\displaystyle\sum_{n\ge0}\frac{(-1)^n}{2n+1}x^{2n+1}](https://tex.z-dn.net/?f=f%28x%29%3Df%280%29%2B%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cfrac%7B%28-1%29%5En%7D%7B2n%2B1%7Dx%5E%7B2n%2B1%7D)
![\implies\tan^{-1}x=\displaystyle\sum_{n\ge0}\frac{(-1)^n}{2n+1}x^{2n+1}](https://tex.z-dn.net/?f=%5Cimplies%5Ctan%5E%7B-1%7Dx%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cfrac%7B%28-1%29%5En%7D%7B2n%2B1%7Dx%5E%7B2n%2B1%7D)